Microcin J25 membrane interaction: Selectivity toward gel phase - Dupuy, Fernando Gabriel (2011)
The interaction of the tryptophan-containing variant of microcin J25, MccJ25 I13W, with phosphatidylcholine membranes was studied by fluorescence spectroscopy techniques. The peptide was able to interact with dimiristoylphophatidylcholine and dipalmitoylphosphatidylcholine liposomes only when the membranes were in gel phase, as was demonstrated by the blue shift of the intrinsic fluorescence of MccJ25 I13W. The binding isotherm showed a cooperative partition of the peptide toward the membrane and the binding constant increased as the temperature decreased and the order parameter increased. No interaction with liquid crystalline membranes was observed. Studies of dynamic quenching of the fluorescence indicated that the peptide penetrated the lipid bilayer and was located primarily in the interfacial region. Our results suggest that MccJ25 I13W interacts with gel phase phospholipids and increases both its own affinity for the bilayer and the membrane permeability of small ions.